Need factors for utilisation of institutional delivery services in Nepal: an analysis from Nepal Demographic and Health Survey, 2011 - Vishnu Khanal; Andy H Lee; Rajendra Karkee (BMJ Open)
Objective This study aims to assess the role of need factors with respect to the utilisation of institutional delivery services in Nepal.Design An analytic study was conducted using a subset of 4079 ever married women from the 2011 Nepal Demographic and Health Survey, which utilised two-stage cluster sampling. Logistic regression with complex sample analysis was performed to evaluate the effects of antenatal care visits and birth preparedness activities on facility delivery.Outcome measures Facility delivery.Results Overall facility delivery rate was low at 36.9% (95% CI 33.5% to 40.2%, SE 1.69). Only half (50.1%) of the women made four or more antenatal care visits while 62.9% (95% CI 59.9% to 65.8%, SE 1.51) did not indicate any of the four birth preparation activities. After adjusting for external, predisposing and enabling factors, women who made more than four antenatal care visits were five times more likely to deliver at a health facility when compared to those who paid no visit (adjusted OR 4.94, 95% CI 3.14 to 7.76). Similarly, the likelihood for facility delivery increased by 3.4-fold among women who prepared for at least two of the four activities compared to their counterparts who made no preparation (adjusted OR 3.41, 95% CI 2.01 to 5.58).Conclusions The perceived need, as expressed by the frequency of antenatal care visits and birth preparedness activities, plays an important role in institutional delivery service utilisation for Nepali women. These findings have implications for behavioural interventions to change their intention to deliver at a health facility.